The Role Of Spiritual And Educational Events In Promoting The Ideas Of Religious Tolerance And International Health. - Ruslan Damirovich , Mustaev; Ilhom Ibragimovich , Tukhtanazarov; Ulugbek Sattarovich, Abdusalomov (Brazilian Journal of Implantology and Health Sciences, 2022)
This article deals with spiritual and enlightenment propaganda in promoting the idea of religious and interethnic tolerance. There is information about the current political and social news in this area.